Fluoride release and uptake in enhanced bioactivity glass ionomer cement ("glass carbomer™") compared with conventional and resin-modified glass ionomer cements - Ammar M. H. R. HASAN; Sharanbir K. SIDHU; John W. NICHOLSON (University of São Paulo, 2019)
Abstract Objectives To study the fluoride uptake and release properties of glass carbomer dental cements and compare them with those of conventional and resin-modified glass ionomers. Materials and Methods Three materials were used, as follows: glass carbomer (Glass Fill), conventional glass ionomer (Chemfil Rock) and resin-modified glass ionomer (Fuji II LC). For all materials, specimens (sets of six) were matured at room temperature for time intervals of 10 minutes, 1 hour and 6 weeks, then exposed to either deionized water or sodium fluoride solution (1000 ppm in fluoride) for 24 hours. Following this, all specimens were placed in deionized water for additional 24 hours and fluoride release was measured. Results Storage in water led to increase in mass in all cases due to water uptake, with uptake varying with maturing time and material type. Storage in aqueous NaF led to variable results. Glass carbomer showed mass losses at all maturing times, whereas the conventional glass ionomer gained mass for some maturing times, and the resin-modified glass ionomer gained mass for all maturing times. All materials released fluoride into deionized water, with glass carbomer showing the highest release. For both types of glass ionomer, uptake of fluoride led to enhanced fluoride release into deionized water. In contrast, uptake by glass carbomer did not lead to increased fluoride release, although it was substantially higher than the uptake by both types of glass ionomer. Conclusions Glass carbomer resembles glass ionomer cements in its fluoride uptake behavior but differs when considering that its fluoride uptake does not lead to increased fluoride release.